2020
DOI: 10.3390/biom10121689
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Major Endogenous FAHFAs in Healthy Human Circulation: The Correlations with Several Circulating Cardiovascular-Related Biomarkers and Anti-Inflammatory Effects on RAW 264.7 Cells

Abstract: Fatty acid esters of hydroxy fatty acids (FAHFAs) are newly discovered long-chain fatty acids. However, the major endogenous FAHFAs in healthy human circulation, their correlation with cardiovascular (CV) biomarkers, and their anti-inflammatory effects have not been investigated and remain unclear. In the present study, a total of 57 healthy subjects were recruited. Liquid chromatography–mass spectrometry (LC-MS) was developed for the simultaneous determination of seven FAHFAs, four long-chain fatty acids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
2
20
1
Order By: Relevance
“…FAHFAs, a new class of endogenous lipids derived from DHA, were first discovered in 2014 and have antidiabetic and anti-inflammatory effects in mammals [ 32 , 33 , 34 ]. Additionally, recent studies have determined that FAHFAs also have cardiovascular protective effects [ 35 ]. Although evidence for the direct interaction between alcohol and FAHFAs is deficient, downregulated FAHFA levels in the ACM group are speculated to be associated with the pathogenesis of myocardial injury induced by chronic alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…FAHFAs, a new class of endogenous lipids derived from DHA, were first discovered in 2014 and have antidiabetic and anti-inflammatory effects in mammals [ 32 , 33 , 34 ]. Additionally, recent studies have determined that FAHFAs also have cardiovascular protective effects [ 35 ]. Although evidence for the direct interaction between alcohol and FAHFAs is deficient, downregulated FAHFA levels in the ACM group are speculated to be associated with the pathogenesis of myocardial injury induced by chronic alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we used glucose and clinical diagnosis to classify our study subjects. Of note, another recent study reported even negative correlation of 9-POHSA and 9-OAHSA with blood glucose in healthy subjects (16). An interpretation of all those studies might be complicated by the fact that different experimental set ups were used and confirmatory experimental studies with a similar design over a longer period are needed to clarify the role of FAHFAs in diabetes and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of FAHFAs has evoked growing interest, as studies have shown that these bioactive lipids might have potent anti-inflammatory properties (3,4,(14)(15)(16). Moreover, they are considered to mediate anti-diabetic effects by stimulating insulin secretion and increasing insulin-stimulated glucose uptake into the adipocyte (3,15).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training induces serum and WAT PAHSA levels in elderly women 11 . Levels of circulating palmitoleic acid ester of 9-HSA (9-POHSA) and oleic acid ester of 9-HSA (9-OAHSA) correlate with protective cardiovascular biomarkers in healthy humans 12 . Thus, FAHFAs have the potential to be important in many physiological and pathophysiological states in humans.…”
Section: Mainmentioning
confidence: 99%